The genome sequence of a metallic wood-boring beetle, Agrilus cyanescens (Ratzeburg, 1837) [version 2; peer review: 2 approved, 1 not approved] - Mark G. Telfer; Dominic Phillips (Wellcome Open Research)
We present a genome assembly from an individual female Agrilus cyanescens (metallic wood-boring beetle; Arthropoda; Insecta; Coleoptera; Buprestidae). The genome sequence is 292.3 megabases in span. Most of the assembly is scaffolded into 10 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 15.91 kilobases in length.